Answer:
x=22
Explanation:
Reorder the terms:
3(-4 + x) = 2(x + 5)
(-4 * 3 + x * 3) = 2(x + 5)
(-12 + 3x) = 2(x + 5)
Reorder the terms:
-12 + 3x = 2(5 + x)
-12 + 3x = (5 * 2 + x * 2)
-12 + 3x = (10 + 2x)
Solving
-12 + 3x = 10 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
-12 + 3x + -2x = 10 + 2x + -2x
Combine like terms: 3x + -2x = 1x
-12 + 1x = 10 + 2x + -2x
Combine like terms: 2x + -2x = 0
-12 + 1x = 10 + 0
-12 + 1x = 10
Add '12' to each side of the equation.
-12 + 12 + 1x = 10 + 12
Combine like terms: -12 + 12 = 0
0 + 1x = 10 + 12
1x = 10 + 12
Combine like terms: 10 + 12 = 22
1x = 22
Divide each side by '1'.
x = 22
Simplifying
x = 22